Trends and research gaps in nano-biochar soil applications: a scientometric analysis - Virú-Vásquez, Paul; Baca-Neglia, Máximo; Badillo-Rivera, Edwin; Césare-Coral, Mary Flor; Castro Pantoja, Jhimy Brayam; Sotelo-Méndez, Alejandrina; Saldivar-Villarroel, Juan; Norabuena Meza, Edgar; Aguirre-Espinoza, Hector; Alvarez-Chancasanampa, Jurgen; Alegría-Arnedo, María Cecilia; Cruz-Martinez, Raymunda Veronica; et al. (Frontiers in Environmental Science, 2026)
Soil contamination caused by heavy metals, organic pollutants, and emerging contaminants (ECs) represents a critical environmental challenge that threatens soil quality, agricultural productivity, and human health. In recent years, biochar and its engineered nanoscale derivative—nano-biochar (NBC)—have emerged as promising, cost-effective amendments for soil remediation. This study conducted a comprehensive scientometric analysis of NBC research applied to soils from 2012 to 2025 using CiteSpace, VOSviewer, and Bibliometrix. The methodology combined co-occurrence mapping, thematic evolution, citation burst detection, and an author-level productivity assessment through h-index, g-index, and m-index evaluation. Additionally, the scientometric analysis was complemented by a focused mini-review addressing three conceptually relevant domains identified in the keyword clusters: adsorption mechanisms, biochar–microbial community interactions, and ecotoxicological risk assessment. Results reveal three distinct developmental phases: (i) an exploratory period (2012–2016) dominated by adsorption and physicochemical optimization; (ii) an expansion phase (2017–2021) integrating nanoparticles, microbial communities, and phytoremediation; and (iii) a recent consolidation (2022–2025) characterized by engineered nanocomposites, multifunctional NBC systems, and the emergence of risk assessment frameworks as a structurally relevant theme. Current hotspots converge on adsorption, microbial-driven remediation, and toxicity reduction, while emerging directions highlight machine-learning-assisted modeling and NBC–microbe interactions. Importantly, findings indicate that risk assessment is transitioning toward a Motor Theme, underscoring the urgent need for deeper ecotoxicological research and the incorporation of NBC within regulatory and policy frameworks that govern soil remediation and sustainable resource management. It is hoped that this work will guide future research trajectories and inform evidence-based decision making for the safe and scalable implementation of NBC technologies.